1988
DOI: 10.1117/12.968434
|View full text |Cite
|
Sign up to set email alerts
|

<title>A Stepper Image Monitor For Precise Setup And Characterization</title>

Abstract: The Stepper Image Monitor(SIM) system tests the resolution and overlay performance of complete stepper systems by measuring the aerial image intensity profile at many wafer locations and focus offsets. Overlay error vectors can be measured with a precision of .021.ím and best focus can be determined to a precision of 0.111m without exposing test wafers. New data will be presented on lens heating effects, along with a simple model. Imagery of high NA steppers will be explored by observing image profiles of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many techniques have been developed to measure the best focus for steppers and scanners. [1][2][3][4][5][6][7][8][9] One technique for monitoring the best focus uses focal dot arrays to create patterns that can be read by the naked eye. 1 The small dots ͑opaque area͒ are drawn on the test reticle.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been developed to measure the best focus for steppers and scanners. [1][2][3][4][5][6][7][8][9] One technique for monitoring the best focus uses focal dot arrays to create patterns that can be read by the naked eye. 1 The small dots ͑opaque area͒ are drawn on the test reticle.…”
Section: Introductionmentioning
confidence: 99%
“…The work by Brunner et al showed that it is feasible to detect the fluorescent signal from the marker in a dry scanner [6][7][8] . Since then, changes are made to the expose area in the scanner that block a direct line of sight.…”
Section: Embodiments For the Fluorescence Detectionmentioning
confidence: 99%
“…That fluorescent markers can indeed be used to measure the positioning and imaging performance of a lithography scanner is shown by Brunner et el. in the 80s of the precious century [6][7][8] . Albeit addressing lens heating, Brunner's experiments did not use at-product-pitch features in the markers.…”
Section: Introductionmentioning
confidence: 99%